Emotional Management In Chronic Disease - Sanjay Kalra,; Hitesh Punyani,; Madhur Verma,; Nitin Kapoor, (Journal of the Pakistan Medical Association, 2025)
Persons living with chronic disease present with a widearray of emotions. These range from affable andaccepting, action- oriented attitude, to anxious, afraid orapathic, adynamic acceptance of disease. Yet others maybe argumentative and angry, or openly aggressive andantisocial. Increasingly, primary care practitioners alsoencounter ‘pseudo academic’ or hyperaware’ patients,who base their knowledge on non scientific social media.This communication describes the various array ofemotions encountered in chronic diseases such asdiabetes and obesity, and suggests an individualizedapproach to deal with them. keywords: Biopsychosocial model, chronic care,emotional health, mental health psychology,psychosocial aspects